121k views
2 votes
Given two functions f(x)=2x+1 and g(x)=−13x−3 , what is the function rule for (f+g)(x)

User Jakupov
by
5.9k points

2 Answers

7 votes

Answer:

- 11x - 2

Explanation:

note that (f + g)(x) = f(x) + g(x)

f(x) + g(x)

= 2x + 1 - 13x - 3 ← collect like terms

= - 11x - 2

User Slushi
by
5.8k points
4 votes

Answer:

(f+g)(x)=5/3x−2

Explanation:

(f+g)(x)=f(x)+g(x)

f(x)=2x+1 + g(x)=−1/3 x−3

add like terms

2x+(-1/3 x)=5/3 x

1+(-3)= -2

so...

(f+g)(x)=5/3 x−2

User Pamala
by
5.6k points